Phytochemical, Antimicrobial and FTIR Analysis of Leaves Extracts of Convolvulus arvensis L.: FTIR Analysis of Extracts of Convolvulus arvensis L. (Biological Sciences - PJSIR, 2023)
Chemical composition, FTIR analysis, and antimicrobial activities of the crude leaf extract of Convolvulus arvensis L. were performed, using five different extracts for the utilization of medicine. FTIR spectra were used to study functional groups by using leaf extracts in different solvents. Alcoholic extracts were found to be richer in bioactive molecules containing alkaloids, phenolic compounds, flavonoids, coumarins, tannins, and glycosides, while the hexane extract exhibited significantly higher antimicrobial activities against Proteus mirabilis (17±0.3mm), Bacillus atrophoeus (11.5±0.3mm), and B. subtilis (12±0.3mm). All the extracts showed significant activity against Gramme-positive bacteria except S. aureus, while the hexane extract showed low antifungal activity against Candida albicans. FTIR spectral analysis shows that the functional groups in all solvents are almost identical. In conclusion, the leaves of C. arvensis contain active biomolecules, and the antimicrobial study encourages the use of these leaf extracts for the treatment of most common microbial diseases (antiseptic) and could be used in the therapeutic and pharmaceutical industries.